Handbook of budgeting - Lalli, William Rea (Wiley, 2012)
No other management tool provides the operational direction that a well-planned budget can. Now in a new edition, this book provides updated coverage on issues such as budgeting for exempt organizations and nonprofits in light of the IRS' newly issued Form 990; what manufacturing CFOs' budgeting needs are; current technology solutions; and updated information on value-based budgets. Controllers, budget directors, and CFOs will benefit from this practical "how-to" book's coverage, from the initial planning process to forecasting to specific industry budgets